Dietary gluten increases natural killer cell cytotoxicity and cytokine secretion. Issue 10 (18th September 2014) - Larsen, Jesper; Dall, Morten; Antvorskov, Julie Christine; Weile, Christian; Engkilde, Kåre; Josefsen, Knud; Buschard, Karsten
<x xml:space="preserve">Abstract</x> Dietary gluten influences the development of type 1 diabetes in nonobese diabetic (NOD) mice and biobreeding rats, and has been shown to influence a wide range of immunological factors in the pancreas and gut. In the present study, the effects of gluten on NK cells were studied in vitro and in vivo. We demonstrated that gliadin increased direct cytotoxicity and IFN‐γ secretion from murine splenocytes and NK cells toward the pancreatic beta‐cell line MIN6 cells. Additionally, stimulation of MIN6 cells led to a significantly increased proportion of degranulating C57BL/6 CD107a+ NK cells. Stimulation of C57BL/6 pancreatic islets with gliadin significantly increased secretion of IL‐6 more than ninefold. In vivo, the gluten‐containing diet led to a higher expression of NKG2D and CD71 on NKp46+ cells in all lymphoid organs in BALB/c and NOD mice compared with the gluten‐free diet. Collectively, our data suggest that dietary gluten increases murine NK‐cell activity against pancreatic beta cells. This mechanism may contribute to development of type 1 diabetes and explain the higher disease incidence associated with gluten intake in NOD mice.